Big Data Analytics and Public Health Strategies in Coping Covid-19 Outbreak - Fitriastuti, Lucia Ika; Vemberi, Yohannes; Zuhri, Saifudin; Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The use of big data analytics plays an important role in determining the public health strategies taken by a country in relation to the Covid-19 pandemic which is currently ongoing worldwide. The objective of this article is to present both conceptual analysis and analysis of the conditions of the Covid-19 pandemic that occurs worldwide to design a framework which shows the relationship between the use of big data analytics and public health strategies to cope with the Covid-19 pandemic. In fact, the public health strategy taken by a country is inseparable from both the public policies strictly taken by its government and the local culture. This way, this paper also discusses the variables of government policies and culture as moderating variables. This article uses the conceptual analysis method and literature review to develop a conceptual model which is followed by proposing three related propositions. In addition, this paper also presents a number of research opportunities as well as the possible research objects, the possible additional variables, and data analysis. This article has implications to assist and provide direction for future research to further examine other interesting topics related to the use of big data analytics in coping with the Covid-19 outbreak. Besides, it also has implications for stakeholders in making decisions and policies to use important variable, i.e. big data analytics, by taking into account government regulations and local culture in dealing with the Covid-19 outbreak.